Penggunaan Tinta Sulam Pada Kecantikan Ditinjau dalam Pandangan Hukum Islam - Helvini, Jeni Putri; Fadhilah, Trimeilinda; El Mahd, Raissa Fakhriyah; Begum, An Najwa Khairunnisa; Ramadhani, Susi (PPSDP Undergraduate Journal of Educational Sciences, 2024)
This research aims to contribute to the Islamic discourse regarding the prohibition of altering Allah’s creation and to enrich the campus library’s collection regarding eyebrow and lip embroidery from the perspective of Islamic law. This research is a normative legal research or based on literature (library research). The approach used in this study is a historical approach, this approach can be used to understand religion that exists in an empirical order or formal form that is prevalent in society. The results obtained from this study are first, embroidery in the sentence is denoted for the act of embroidering or embroidering clothes, both eyebrow embroidery and lip embroidery are not much different from using tattoos, but when viewed from the material, it uses semi-permanent ink, so it is considered haram. Second, the use of embroidery is prohibited in Islamic Law as it falls under the category of altering Allah’s creation. Third, the materials used for eyebrow and lip embroidery can prevent water from reaching the skin during ablution (wudhu).